Problem Based Learning Terintegrasi STEM Di Era Pandemi Covid-19 Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Clarissa Desyana Putri; Indarini Dwi Pursitasari*; Bibin Rubini (Program Studi Magister Pendidikan IPA Program Pascasarjana Universitas Syiah Kuala, 2020)
The COVID-19 pandemic has changed the learning system in schools. The learning that initially took place in class spontaneously turned into online learning. This change requires teachers to be more creative in designing learning. This study aims to improve students' critical thinking skills through online problem-based learning integrated into science, technology, engineering, and mathematics (PBL-STEM). The research was conducted on students of class X IPA (Natural Science) in a high school in Cianjur with a Non-Equivalent Pretest-Posttest Control Group design. The research data were collected using a test of critical thinking skills in six valid essay questions with a reliability coefficient of 0.913. Besides, students' responses to the application of PBL-STEM learning were collected through a questionnaire. The collected data were processed descriptively and inferentially. The results showed that the online application of PBL-STEM went well, and there was an increase in critical thinking skills with an N-gain of 72%. The highest gain is on the indicator of explanation, and the lowest is evaluation. The results of the significance test showed that the increase in students' critical thinking skills through PBL-STEM learning was more significant than PBL learning. Students also responded well to the implementation of PBL-STEM in learning during the COVID-19 pandemic by 81%.